PEMBERDAYAAN TANAMAN LOKAL SEBAGAI PRODUK MINUMAN DALAM PENGEMBANGAN TEMPAT WISATA TAMAN BRONJONG SRIMARTANI PIYUNGAN BANTUL - M.Fathurrahman Nurul Hakim; Erlangga Brahmanto; Atun Yulianto (STIE Pariwisata API Yogyakarta, 2020)
Piyungan Bantul District, Yogyakarta has a very interesting natural tourism potential where there are many plants that can be developed into an attraction, one of which is located in the village of Wanojoyo Kidul, there is a tourist spot called Taman Bronjong. As the name implies, Bronjong is water retaining so that the land on the banks of the river is not eroded by river currents, especially in Kali Gawe. Taman Bronjong has direct views of the Bukit Bintang and has a child-friendly stream. The research method used in this research process is descriptive qualitative supported by quantitative data. The observations show that in this garden there are many plants that can be used for the manufacture of local beverage products such as lemongrass, ginger, turmeric, cinnamon, kencur. With the potential possessed by Taman Bronjong, researchers aim to empower local plants as beverage products in order to develop tourist attraction in the area.